Comparison between the Performance of Vertical and Inclined Grouted Soil Anchors in Sandy Soils under Static Axial Load - F. Mekki (Algerian Journal of Research and Technology (AJRT), 2022)
Grouted soil anchors referenced simply as ground anchors are elements installed in soil or rock. They allow the transmission of the pullout load to soil layers at a greater depth. They can be placed vertically, or in an inclined position according to the orientation of the loads and the type of structures. This paper presents a comparison between the performance of vertical and inclined grouted soil anchors subjected to static axial loading placed in three sandy soils by using the kinematic approach of limit analysis. A parametric study was performed to identify the effect of the bonded length and the diameter of bonded length on the collapse load of vertical and inclined grouted soil anchors. Results obtained from the present theoretical study showed that the highest capacity could be achieved when the grouted soil anchor is in a vertical orientation. The study also revealed that the pullout load capacity of inclined grouted soil anchor increases with an increase in the bonded length, the diameter of bonded length and the density of sandy soils. In addition, the bonded length significantly affects the ultimate pullout capacity of vertical grouted soil anchor but the diameter of bonded length has no effect on the ultimate load of grouted soil anchor placed vertically and the density of sandy soils has a decreasing effect on the vertical load capacity.